VISUAL REPRESENTATIONS ANALYSIS OF SENIOR HIGH SCHOOL BIOLOGY TEXTBOOKS ABOUT THE HUMAN MOVEMENT SYSTEM - Antasena, Muhamad Yafi B.; Agung Wijaya Subiantoro (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
This study aims to identify the proportions and types of visual representations in Grade XI Biology textbooks, specifically on the topic of the Human Locomotion System. Visual content in Biology textbooks plays a crucial role in facilitating students’ understanding of biological concepts; however, previous studies have shown that such content remains limited in depth and rarely connects biological material to real-life contexts. The objective of this research was to examine the functions and forms of visual representations in selected textbooks, and to evaluate their alignment with principles of effective visual representation. Employing a qualitative content analysis approach, four textbooks were analyzed using a classification framework that classified the visual representations by their function (decorative, illustrative, explanatory, complementary) and by their form (e.g. illustrations, diagrams, tables, maps). The results revealed that visual representations were predominantly illustrative in both function and form across all Biology textbook samples. Among the samples, the YT textbook demonstrated the highest quantity and diversity of visual content, while KM had the fewest. These findings suggest that the textbooks have not fully adhered to the principles of effective visual representation, which may limiting students’ understanding of complex biological concepts. It is recommended that future editions increase both the quantity and variation of visual content to enhance pedagogical effectiveness and promote deeper learning.